Ortega y Gasset: Religion and the Problem of Spain - Moreno Fernández, Agustín (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Ortega didn’t study religion as a philosophical problem specifically. However, throughout his work, we can find a lot of references about religion. Particularly during his youth, some of them refer to his personal way of thinking about religion: life affirmation, respect and fidelity to self and his circumstance. Ortega was inspired by Goethe or Renan but, in order to understand this religious conception, we must look into the religious problems in Spain and his scientific and cultural backwardness with regard to Europe